Biomassa de Rubrivivax gelatinosus na criação de frangos de corte: desempenho animal e cor dos produtos - Avanço, S. V. [UNESP] (2014)
The phototrophic bacterium Rubrivivax gelatinosus has been used experimentally for the depollution of industrial effluents from broiler and fish slaughterhouses, resulting in a biomass containing oxycarotenoids, substances that impart color and protection against to oxidative reactions. This work aimed to check the effect of R. gelatinosus biomass added into broiler chickens' feed on animal performance and meat/skin color. Two hundred Cobb 500 male chicks were randomly divided into 20 boxes to receive, from the 36th to the 45th day of rearing, 4 treatments with different amounts of biomass in the diets (T1 [control] - 0g/kg; T2 - 1g/kg; T3 - 2g/kg; T4 - 3g/kg), in 5 replicates. Chickens and rations were weighted at the beginning of the rearing time and at the end of each growth phase to assess animal performance. At the end of the experiment (45 days), 20 birds from each repetition were slaughtered for the evaluation of the objective color (L - lightness, C - chroma, h - hue) on skin and meat of breast and thigh. Statistical analyses comprised ANOVA, t test for means comparison and regression analysis, at 5% significance level. Weight gain and feed consumption did not differ statistically (P>0.05), while feed conversion was better for T1. Lightness of meat and skin increased significantly in the treatments with the biomass supplementation. Hue angle of meat and skin increased towards yellow until 2g biomass/kg and towards red at 3g/kg. Chroma was only influenced by the presence of the biomass in thigh meat. It was concluded that the addition of the biomass up to 3g/kg was not harmful to birds' performance and was efficient to cause changes in the color of broiler skin and meat.